Analisis Persediaan Bahan Baku Untuk Efisiensi Biaya Menggunakan Metode EOQ DAN POQ: (Studi Kasus : PT. XYZ) - Lumbantobing, Iman jaharia; Pratiwi, Irnanda; Aprilyanti, Selvia (Universitas Nusantara PGRI Kediri, 2023)
This research was conducted to control inventory at PT.XYZ, which is a company engaged in ready-mixed concrete industry. The company has only used conventional methods in procuring raw materials. Based on the data observed over the past year, the company has incurred cost wastage on raw materials due to excessive ordering. The method used in this study is the economic order quantity (EOQ) and period order quantity (POQ) to determine the optimal ordering size and period by minimizing the total inventory costs that include ordering and holding costs. The study was conducted by collecting ordering and inventory data over the past year and analyzing the data using EOQ and POQ methods. The results showed that by applying the EOQ method, the company spent a total of Rp. 219.870.807 for all raw materials, while with the POQ method, the company spent a total of Rp. 373.361.217 for all raw materials. This indicates that the EOQ method produces lower total costs compared to the POQ method.